The novel p.Ser263Phe mutation in the human high‐affinity choline transporter 1 (CHT1/SLC5A7) causes a lethal form of fetal akinesia syndrome. Issue 10 (12th July 2019) - Banerjee, Mayukh; Arutyunov, Denis; Brandwein, Daniel; Janetzki‐Flatt, Cassandra; Kolski, Hanna; Hume, Stacey; Leonard, Norma Jean; Watt, James; Lacson, Atilano; Baradi, Monica; Leslie, Elaine M.; Cordat, Emmanuelle; et al.
Abstract: A subset of a larger and heterogeneous class of disorders, the congenital myasthenic syndromes (CMS) are caused by pathogenic variants in genes encoding proteins that support the integrity and function of the neuromuscular junction (NMJ). A central component of the NMJ is the sodium‐dependent high‐affinity choline transporter 1 (CHT1), a solute carrier protein (gene symbol SLC5A7 ), responsible for the reuptake of choline into nerve termini has recently been implicated as one of several autosomal recessive causes of CMS. We report the identification and functional characterization of a novel pathogenic variant in SLC5A7, c.788C>T (p.Ser263Phe) in an El Salvadorian family with a lethal form of a congenital myasthenic syndrome characterized by fetal akinesia. This study expands the clinical phenotype and insight into a form of fetal akinesia related to CHT1 defects and proposes a genotype‐phenotype correlation for the lethal form of SLC5A7 ‐related disorder with potential implications for genetic counseling.